APPLICATION OF PLACEBO EFFECT INTERFACE DESIGN IN IMPROVING THE USER EXPERIENCE - Wang, Shao Feng (PEOPLE: International Journal of Social Sciences, 2019)
The Internet is a virtual architecture of the real world. Traditional designers often transplant real-life experiences into Internet product design to reduce learning costs. The user interface is the language of communication between the two worlds. The user experience can make the virtual world communicate more smoothly with the real world. It is difficult for designers to balance user needs with business needs if they rely solely on traditional life experiences. Because both are competing for users' time. Thus, we can balance the needs of both parties by using the placebo effect to reduce the anxiety of the user waiting. This article takes the loading method of APP startup page as an example, from the perspective of Internet interface design and user experience, to explore how to optimize the user experience and reduce anxiety. Using the questionnaire method and the sounding thinking method to obtain the user's data. The correlation between different requirements was obtained by using the Likert scale and One-factor dependent sample ANOVA. The Kano model was used to classify the data into different levels of requirements. This study has contributed to the study of user experience in optimizing the loading interface.